Nuclear effects on the transverse momentum spectra of charged particles in pPb collisions at root s(NN)=5.02 TeV - (:unkn) unknown (SPRINGER, 2015)
Transverse momentum spectra of charged particles are measured by the CMS experiment at the CERN LHC in pPb collisions at root s(NN) = 5.02 TeV, in the range 0.4 < pT < 120 GeV/c and pseudorapidity |eta(CM)| < 1.8 in the proton-nucleon center-of-mass frame. For p(T) < 10 GeV/c, the charged-particle production is asymmetric about eta(CM) = 0, with smaller yield observed in the direction of the proton beam, qualitatively consistent with expectations from shadowing in nuclear parton distribution functions (nPDF). A pp reference spectrum at root s = 5.02 TeV is obtained by interpolation from previous measurements at higher and lower center-of-mass energies. The p(T) distribution measured in pPb collisions shows an enhancement of charged particles with p(T) > 20 GeV/c compared to expectations from the pp reference. The enhancement is larger than predicted by perturbative quantum chromodynamics calculations that include antishadowing modifications of nPDFs.
Keywords: PARTON; SATURATION